Gastrointestinal Hemorrhage With Gastritis and Pancolitis as the Sole Presentation for Granulomatosis With Polyangiitis Flare. Issue 12 (19th December 2022) - Khan, Sarah; Alkhayyat, Motasem; Albakri, Almaza; Setrakian, Sebouh; Falloon, Katherine; Abou Saleh, Mohannad; Ajayi-Fox, Patricia
ABSTRACT: Granulomatosis with polyangiitis (GPA), previously known as Wegener granulomatosis, is a rare small vessel vasculitis affecting mainly Whites. The prevalence of GPA in the United States is estimated to be 3 of 100, 000 individuals. Classically, GPA affects upper airways, lungs, and kidneys, with the upper airways being the most common site. Occasionally, other organs affected by GPA include eyes, skin, joints, and the nervous system. The gastrointestinal system is rarely affected; however, some cases have been reported. In this case report, we present a patient with hemorrhagic gastritis and pancolitis consistent with GPA and discuss features from the literature of gastrointestinal manifestations in patients with GPA.